2008
DOI: 10.1111/j.1365-2052.2007.01695.x
|View full text |Cite
|
Sign up to set email alerts
|

A muscle transcriptome analysis identifies positional candidate genes for a complex trait in pig

Abstract: Muscle tenderness is an important complex trait for meat quality and thus for genetic improvement through animal breeding. However, the physiological or genetic control of tenderness development in muscle is still poorly understood. In this work, using transcriptome analysis, we found a relationship between gene expression variability and tenderness. Muscle (longissimus dorsi) samples from 30 F(2) pigs were characterized by Warner-Bratzler Shear Force (WBSF) on cooked meat as a measurement of muscle tenderness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 61 publications
2
47
0
3
Order By: Relevance
“…The most significant molecular and cellular functions for tenderness were protein synthesis, cellular assembly, and cell cycle (Table 2), emphasising the importance of cellular growth-related pathways in defining tenderness. Lobjois et al (2008) profiled gene Fig. 3.…”
Section: Growth and Development Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most significant molecular and cellular functions for tenderness were protein synthesis, cellular assembly, and cell cycle (Table 2), emphasising the importance of cellular growth-related pathways in defining tenderness. Lobjois et al (2008) profiled gene Fig. 3.…”
Section: Growth and Development Genesmentioning
confidence: 99%
“…It is estimated that 80-90% of all cellular proteins are ultimately degraded by the proteasome pathway and many studies report enhanced proteasome expression during muscle atrophy (Goll et al, 2008). While, Lobjois et al (2008) in studies of tenderness in pork, identified differential expression of only one ubiquitination process gene (CDC34) in relation to shear force, their studies focused on ultimate tenderness, whereas our samples differed in early post mortem and not ultimate tenderness, suggesting that the proteasome may be important for rate of tenderisation. Bovine proteomic studies have shown that 27s proteasome subunit abundance is correlated with shear force in bovine Musculus rectus abdominus (Oury, Picard, Briand, Blanquet, & Dumont, 2009), that muscle concentrations of the proteasome complex are stable over the post mortem period (Dutaud et al, 2006), and that laboratory inhibition of the bovine proteasome impaired the degradation of structural and sarcoplasmic proteins (Houbak, Ertbjerg, & Therkildsen, 2008).…”
Section: Myofibrillar and Proteolytic Genesmentioning
confidence: 99%
“…Several SNPs (TNNT3, CYP2E, CAST A499C), which showed additive effects on analysed traits in our study, were shown (by other authors) to be also associated with meat quality traits, e.g. tenderness, pH, intramuscular fat content, muscle colour, scatole content (Lobjois et al 2008;Amills et al 2005;Lin et al 2006;Arnyasi et al 2006;Krzecio et al 2005). They are promising candidates for simultaneous improvement of both types of traits (quantity and quality of meat), which is one of the most challenging tasks of marker assisted selection applied to pig breeding.…”
Section: Resultsmentioning
confidence: 90%
“…The causal polymorphism has not yet been identified. Among the 272 genes with a regulated expression by at least one eQTL, five genes (ACOX1, FKBP8, LDHA, NEB, and SEPW1) have their expression level correlated with the Warner-Bratzler SF (Lobjois et al, 2008); no cis-eQTL was identified for these genes.…”
Section: Eqtl In Pigmentioning
confidence: 96%
“…Among these genes, 12 were localized on four chromosome regions of interest (QTL) on chromosomes 2, 6 and 13. This enabled us to propose positional and functional candidate genes to explain the effects observed by these QTL (Lobjois et al, 2008). About half of these genes are unknown or involved in unexpected functions related to MQ traits.…”
Section: Eqtl In Pigmentioning
confidence: 99%